Konformitas Teman Sebaya, Dukungan Sosial, dan Motivasi Belajar pada Remaja Indonesia - Ali Anwar; Jalaludin; Muh Musyahidin (MUADDIB: Jurnal Pendidikan Agama Islam, 2026)
Learning motivation plays a critical role in students’ academic success, particularly in socially dynamic environments where peer influence is increasingly prominent. This study aims to examine the direct and interactive effects of peer conformity and social support on adolescents’ learning motivation within an integrative structural framework. A quantitative explanatory design was employed, involving 402 secondary school students in Indonesia, with data analyzed using Variance-Based Structural Equation Modeling (PLS-SEM). The results demonstrate that both peer conformity and social support have significant positive effects on learning motivation (β = 0,310, p < 0,05; β = 0.47, p < 0,05, respectively). Crucially, the interaction between peer conformity and social support is found to be significant (β = 0,180, p < 0,05), confirming that social support acts as a moderator that strengthens the positive impact of conformity on academic engagement. This study contributes theoretically by bridging fragmented literature into a comprehensive model of social dynamics and offers practical implications for educators to design socially responsive learning strategies that leverage peer environments.